Problematika Perkawinan Beda Agama di Indonesia dalam Perspektif Hak Asasi Manusia - Gafrila Jenifer Runtu; Wenly R. J. Lolong; Hendrasari B. R. Rawung (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research discusses the problems faced in the implementation of interfaith marriages in Indonesia by reviewing the extent to which national legal provisions are in line with or contradict the principles of Human Rights (HAM). The focus of the research is an evaluation of the legal framework governing interfaith marriages and whether the legal arrangements are in accordance with the principles of human rights and how they impact on the fulfillment of everyone's rights. The research method used is normative legal research with a statutory approach and a case approach. Data were collected through a literature study of primary legal materials such as the Marriage Law, Population Administration Law, and international human rights instruments, as well as secondary legal materials such as journals and court decisions. Data analysis was conducted qualitatively to identify gaps between national law and human rights principles. The results show that the provision of Article 2 Paragraph (1) of the Marriage Law that requires religious equality creates discrimination and legal uncertainty for couples of different religions. Although several court decisions have accommodated interfaith marriages, Supreme Court Circular Letter No. 2 of 2023 has tightened the restrictions. This study recommends the revision of the Marriage Law to accommodate a religion-neutral civil registration mechanism, as well as harmonization with international human rights instruments such as the Universal Declaration of Human Rights and the Covenant on Civil and Political Rights.